2022
DOI: 10.3390/molecules27061787
|View full text |Cite
|
Sign up to set email alerts
|

Asparagopsis Genus: What We Really Know About Its Biological Activities and Chemical Composition

Abstract: Although the genus Asparagopsis includes only two taxonomically accepted species, the published literature is unanimous about the invasive nature of this genus in different regions of the globe, and about the availability of large amounts of biomass for which it is important to find a commercial application. This review shows that extracts from Asparagospsis species have already been evaluated for antioxidant, antibacterial, antifungal, antiviral, antifouling, cytotoxic, antimethanogenic and enzyme-inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 160 publications
(205 reference statements)
0
7
0
Order By: Relevance
“…Asparagopsis armata and A. taxiformis are two red algae known for their production of halogenated molecules [ 26 , 27 , 28 , 29 ]. Several studies reported differences in the concentration of some targeted halogenated molecules between the different life stages of the genus [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asparagopsis armata and A. taxiformis are two red algae known for their production of halogenated molecules [ 26 , 27 , 28 , 29 ]. Several studies reported differences in the concentration of some targeted halogenated molecules between the different life stages of the genus [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…355 Several rst total syntheses of red algal metabolites were published in 2022, including those of C 15 acetogenins dehydroitomanallene B, 356 Z-906 and E-ocellenyne 907, which also established their absolute congurations, 357 sesquiterpenoid laurencenone C 358 and thysiferol-type triterpenoid saiyacenol A. 359 A review of the metabolites from the possibly invasive genus Acanthophora and of Asparagopsis, respectively, have been published, 360,361 as has a summary of red algal compounds with skin whitening cosmeceutical potential. 362 The role of carotenoids in the adaptation of the intertidal red alga Neopyropia yezoensis towards daily desiccation has been investigated.…”
Section: Red Algaementioning
confidence: 99%
“…A review of the metabolites from the possibly invasive genus Acanthophora and of Asparagopsis , respectively, have been published, 360,361 as has a summary of red algal compounds with skin whitening cosmeceutical potential. 362…”
Section: Red Algaementioning
confidence: 99%
“…The significance of the genus Asparagopsis derives from its intricate chemical composition and the potential utility of its constituents (Ponte et al, 2022). Asparagopsis species have been documented to produce an extensive array of bioactive compounds, polysaccharides, lipids, proteins, sterols, and bromoform (Feĺix et al, 2021).…”
Section: Introductionmentioning
confidence: 99%